Drilling holes in Mars. - Zorpette, G.
This paper describes an electric drill that will make the first holes in rocks on Mars. Attached to a robotic arm on the mission's roving vehicle, the Rover Rock Abrasion Tool will bore holes 45 mm in diameter and 5 mm deep in Mars rocks. To make each indentation, Honeybee has been allotted only 32.5 Wh. The drill itself with its diamond bit weighs just 0.7 kg
Keywords: 0.7 kg; 32.5 Wh; 45 mm; 5 mm; Honeybee robotic electric drill; Mars; Rover Rock Abrasion Tool; Diamond bit; Robotic arm; Roving vehicles